Efeitos de regras discrepantes das contingências apresentadas por falantes com diferentes níveis de autoridade sobre a manutenção do seguimento de regras - Lorbieski, Letícia (Universidade Federal de São Carlos, 2023)
Considering the context of the Covid-19 pandemic, in which rules regarding the precautions with the pandemic have been presented inconsistently by different authorities (e.g., health organizations versus political leaders), the objective of the study was to evaluate the effects of presenting discrepant rules spoken by speakers with different levels of authority (adult teacher and child) on children's maintenance of rule compliance, as well as determining whether the level of authority differentially affects the following of discrepant rules. Twelve children aged 7 to 9 years participated in the study and were exposed to a Matching To Sample (MTS) choice task in a single session with 100 trials divided into 5 blocks. In blocks 1, 3 and 5, the rule presented by the computer corresponded to the contingency. In blocks 2 and 4, a rule that differed from the contingencies was presented by speakers with different levels of authority. To control for the order effect, half of the participants were first exposed to the presentation of the discrepant rule by the higher level of authority figure, the adult teacher, and then by the lower level of authorityfigure, the child, while the other half were exposed to the opposite order. The results indicated that the levels of authority manipulated in this study did not differentially influence the maintenance of the discrepant rule-following. Although the average number of correct answers for the lowest level of authority (child) was lower than for the highest level, the difference between them was not statistically significant. It was argued that, considering the authority variable as a social variable, the online procedure may not have favored the establishment of speakers as authorities of different levels.
Effects of discrepant rules presented by speakers with different levels of authority on the maintenance of rule-following
Keywords: Autoridades; Comportamento controlado por regras; Regra discrepante; Sensibilidade comportamental às contingências; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO